Two-Step Procedure for Liquid-Salt-Cooled-Reactor Analysis. (2nd December 2018) - Gentry, Cole; Kim, Kang Seog; Maldonado, G. Ivan
Abstract: This paper presents the development of a lattice physics–to–core simulator two-step procedure for the rapid analysis of the Advanced High Temperature Reactor (AHTR). Lattice physics, reflector, and control blade models were developed from which cross-section libraries could be generated for a nodal core simulator. Few-group structures for the core simulator were also generated to account for the neutronic characteristics of AHTR. After developing the AHTR two-step procedure, cross-section libraries were generated using the SERPENT continuous-energy Monte Carlo code. These libraries were then used in the core simulator NESTLE to perform full-core calculations, which were in turn benchmarked against reference SERPENT full-core models. Benchmarking results showed reasonable accuracy of the developed two-step procedure but revealed an inherent inadequacy in the one-dimensional radial reflector model and showed a likely need for a greater number of energy groups than were used in this study.